2015
DOI: 10.17576/jpen-2015-4002-12
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Students’ Learning Problems in Hypothesis Testing

Abstract: Hypothesis testing is an important tool of statistical inference and is taught in most introductory

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…Incorrect identification of the test statistic formula and incorrect computation of the calculated value of the test statistic were moderately-frequent mistakes. These results are similar to the typology identified by Link (2002) and Krishnan and Idris (2015). The most frequent mistakes in testing for a single population mean were found to be the incorrect taking of the decision and drawing of the conclusion, followed by incorrect formulation of H 0 and H 1 , incorrect identification of one/two tailed test, and incorrect identification of the critical value.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Incorrect identification of the test statistic formula and incorrect computation of the calculated value of the test statistic were moderately-frequent mistakes. These results are similar to the typology identified by Link (2002) and Krishnan and Idris (2015). The most frequent mistakes in testing for a single population mean were found to be the incorrect taking of the decision and drawing of the conclusion, followed by incorrect formulation of H 0 and H 1 , incorrect identification of one/two tailed test, and incorrect identification of the critical value.…”
Section: Resultssupporting
confidence: 86%
“…she suggested that statistical instruction should focus more on the development of student understanding of overall statistical hypothesis testing, particularly on the development of understanding of the logic of indirect reasoning and its role in statistical hypothesis testing, along with uncertainty and variability. Krishnan and Idris (2015) provided an overview of the problems faced by students in the learning of hypothesis testing. They suggested a classification of twenty-one distinct types of mistakes in hypothesis testing under six broad groups, viz.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While hypothesis testing is an important tool of statistical inference (Krishnan & Idris, 2015), its use to interpret experimental data has received criticism (Motulsky, 2014;Nickerson, 2000;Nuzzo, 2014) due to the common misunderstandings by both scientists and students when using this method (Batanero, 2000;Dolor & Noll, 2015;Vallecillos, 2000), such as the meaning behind the p-value. Rather than abandon this method of inference entirely, researchers have called for improving the education and understanding of hypothesis testing.…”
Section: Introductionmentioning
confidence: 99%
“…Students also did not understand the purpose of the problem (Diniyah, Akbar, Akbar, Nurjaman, & Bernard, 2018). Furthermore, Link (Krishnan & Idris, 2015) said students have trouble when stating the hypotheses. Students did not understand the definitions of hypotheses (Sotos, Vanhoof, Noortgate, & Onghena, 2009).…”
Section: Idiosyncratic Reasoningmentioning
confidence: 99%